The Influence of Students' Satisfaction in Online Learning and Its Implications on Students' Motivation and Learning Achievement - Pangoloan Soleman Ritonga; Zona Octarya; Paijan Rambe (STAI Hubbulwathan Duri, 2023)
This study aims to describe the process of lectures conducted online, namely how the influence of online learning service satisfaction on learning motivation and student achievement of a state Islamic university in Riau. The data collection method in this study was a survey in the form of a questionnaire which was distributed to students with a total sample of 246 people who were distributed to all faculties. Data analysis using SEM Path Analysis 3.0 and SPSS 21. The results showed that satisfaction in online learning was in the satisfied category, motivation was quite high, and achievement was very high, and the effect of satisfaction in online learning on learning motivation was significant in the 2-sided test (t table = 1.97) with a t-statistic value of 9.525 or greater than t table, and the p-value is smaller than alpha 5% (0.000 0.05). The effect of satisfaction in online learning on learning achievement is significant in the 2-sided test (t table = 1.97) with a t-statistic value of 0.856 which is smaller than the t table, and the p-value is smaller than alpha 5% (0.392 0.05. The effect of learning motivation on learning achievement is significant in the 2-sided test (t table = 1.97) with a t-statistic value of 3.090 greater than the t table, and the p-value is less than 5% alpha (0.002 0.05). The effect of satisfaction in online learning on achievement is significant in the 2-sided test (t table = 1.97) with a t-statistic value of 2.999 greater than the t table, and nil ai p is smaller than alpha 5% (0.003 0.05). The results of the research above indicate that satisfaction in online learning has a significant effect on learning achievement through student learning motivation at university.